The Causal Relationship of Tourism and The Selected Macroeconomic Variables With Economic Growth - Cheam, Chai Li (2012)
The world is making tourism its cash cow. So is Malaysia. Currently, tourism is Malaysia’s important foreign exchange earner, second only to manufacturing. Tourism, one of the world’s largest and fastest growing industries is a strategic factor for economic growth. Since the empirical results associated with Granger causality among economic growth, tourism and exports within neoclassical framework are inconsistent, the present study sets out to show that tourism has a role in economic growth using the Malaysian context by utilizing the selected macroeconomic variables of physical capital, education, health and exports as the control variables from 1974-2010. The objectives are to determine 1) the long run relationships, 2) the short run relationships, 3) the long run and short run Granger causality, 4) the long run triangular relationships and 5) the speed of adjustment for economic growth. The study employs econometric techniques such as unit roots, Johansen cointegration, Vector Error Correction Model (VECM) within Granger causality. Results from Johansen cointegration show all the variables are positive and statistically significant to growth except exports and government tourism expenditure. Short run relationships reveal only tourism variables are significant and positively related to growth. The long run Granger causality in VECM show bidirectional relationship among economic growth, tourism receipts and health; while unidirectional causalities are found for the rest of the variables to growth. Interestingly, the selected macroeconomic variables and government tourism expenditure precede tourism receipts while tourism receipts cause health–all these in turn indirectly lead to economic growth thus showing that triangular relationships exists. The speed of adjustment shows a high coefficient when there is a state of disequilibrium. Besides enhancing the present knowledge, the findings also suggest to policy makers to further improve and sustain tourism and the selected macroeconomic variables in order to generate greater economic growth.